Orienting of visual attention in aging. (October 2016) - Erel, Hadas; Levy, Daniel A.
Highlights: Orienting attention in space enables effective perception and action. Orienting of attention is sometimes reported to be affected by healthy aging. Aging effects on orienting are specific to certain task, cue, and timing conditions. Aging effects on orienting may be a function of ancillary cognitive factors. Multiple brain substrates of orienting may explain the diversity of aging effects. Abstract: Changes in attention are among the most important cognitive shifts associated with aging, with implications for maintenance of vocational competencies, participation in social interactions, and successful execution of activities of daily living. An important facet of attention is orienting, the ability to selectively attend a location or modality and thereby engender perceptual augmentation. Orienting also involves shifting of the focus of attention in response to unanticipated salient events. Aging may impact orienting through a variety of neurocognitive mechanisms and the interactions between them. We review findings regarding factors that mediate the impact of aging on orienting, including overt vs. covert attending, exogenous vs. endogenous processes, orienting benefits vs. reorienting costs, cue-target onset asynchrony (SOA), post-orienting task factors, and stage of aging. We also consider aging-related changes in the brain substrates of orienting, including cortical and white matter integrity, laterality, connectivity, neuromodulatory functions, and compensatory activity. Taken together, these findings suggest that healthy aging impacts performance on orienting tasks less through direct effects than via interactions with additional cognitive processes.